Prognostic Value of the Preoperative Neutrophil to Lymphocyte Ratio in Resectable Gastric Cancer - Hsu, Jun-Te (Medicine (Baltimore), 2015)
This study aimed to investigate the prognostic value of the preoperative neutrophil to lymphocyte ratio (NLR) in resectable gastric cancer (GC). This was a retrospective review of 1030 patients with resectable GC managed between 2005 and 2011. Patients were stratified into 2 groups, those with a preoperative NLR >3.44 and those with a preoperative NLR ≤3.44. Clinicopathological data affecting patient prognosis were collected prospectively and analyzed. The high NLR (>3.44) group had a higher proportion of a platelet to lymphocyte ratio >132, tumor size >4.8 cm, T4 lesions, metastatic tumors, a ratio of metastatic to examined lymph nodes >0.18, positive resection margins, and presence of vascular or lymphatic invasion than the low NLR (≤3.44) group. Patients with a high preoperative NLR had significantly lower 3- and 5-year overall survival rates than those with a low preoperative NLR (55.1% vs 71.0% and 47.2% vs 64.1%, respectively; P < 0.001). Preoperative NLR was a prognostic factor for resectable GC in multivariate analysis. More aggressive tumor behavior was observed in patients with resectable GC with a high preoperative NLR than in those with a low preoperative NLR. High preoperative NLR was an independent unfavorable prognostic factor. Measurement of this ratio may serve as a clinically accessible and useful biomarker for patient outcomes.